Effect of Lockdown Period of COVID-19 Pandemic on Maternal Weight Gain, Gestational Diabetes, and Newborn Birth Weight - Collins-Smith, Ana; Prasannan, Lakha; Shan, Weiwei; Dori, Ezra; Katzow, Michelle; Blitz, Matthew J. (American Journal of Perinatology, 2022)
Objective This study aimed to determine whether the lockdown period of the initial novel coronavirus disease 2019 (COVID-19) surge in New York affected gestational weight gain (GWG), newborn birth weight (BW), and the frequency of gestational diabetes mellitus (GDM). Maternal and newborn outcomes during the first wave of the pandemic were compared with those during the same timeframe in the previous 2 years.Study Design Retrospective cross-sectional study of all live singleton term deliveries from April 1 to July 31 between 2018 and 2020 at seven hospitals within a large academic health system in New York. Patients were excluded for missing data on: BW, GWG, prepregnancy body mass index, and gestational age at delivery. We compared GWG, GDM, and BW during the pandemic period (April–July 2020) with the same months in 2018 and 2019 (prepandemic) to account for seasonality. Linear regression was used to model the continuous outcomes of GWG and BW. Logistic regression was used to model the binary outcome of GDM.Results A total of 20,548 patients were included in the study: 6,672 delivered during the pandemic period and 13,876 delivered during the prepandemic period. On regression analysis, after adjustment for study epoch and patient characteristics, the pandemic period was associated with lower GWG (β = −0.46, 95% confidence interval [CI]: −0.87 to −0.05), more GDM (adjusted odds ratio [aOR] = 1.24, 95% CI: 1.10–1.39), and no change in newborn BW (β = 0.03, 95% CI: −11.7 to 11.8) compared with the referent period. The largest increases in GDM between the two study epochs were noted in patients who identified as Hispanic (8.6 vs. 6.0%; p < 0.005) and multiracial/other (11.8 vs. 7.0%; p < 0.001).Conclusion The lockdown period of the pandemic was associated with a decrease in GWG and increase in GDM. Not all groups were affected equally. Hispanic and multiracial patients experienced a larger percentage change in GDM compared with non-Hispanic white patients.Key Points
Keywords: lockdown; sheltering in place; stay at home; COVID-19; weight gain; pregnancy; gestational diabetes; birth weight